Effects of Replacing Alfalfa Hay with Amaranthus caudatus Hay on Digestibility, Methane Emissions, and Microbial Protein Efficiency in Ruminant Diets - Özkan, ÇÖ; Selçuk, B; Bakir, T; Bilal , Y; Kamalak, A (Journal of the Hellenic Veterinary Medical Society, 2025)
The study aimed to assess the impact of substituting alfalfa hay with Amarant (Amaranthus caudatus) hay in ruminant diets on fermentation parameters. Using in vitro gas production, diets with Amaranth hay at 0%, 10%, 20%, and 30% were formulated, maintaining isocaloric and nitrogenic levels. While methane (CH4) production remained unchanged, notable effects were observed on true digestible dry matter (TDDM), true digestibility (TD), gas and methane production per digested dry matter (DM), and microbial protein. Substituting alfalfa with Amaranth hay favored microbial protein production over gas and methane, suggesting potential replacement up to 30%. This substitution reduced methane production and enhanced microbial protein. Further in vivo experiments are necessary to evaluate its impact on feed intake and overall animal production.